Accuracy and reliability of different approaches for the assessment of pelvic floor muscle strength: A systematic review - Alisha Rai; Nidhi Sharma; Sanjeev Kumar Jain; Astha Lalwani; Sonika Sharma (Wolters Kluwer Medknow Publications, 2023)
There had been various methods employed for the evaluation of pelvic floor muscle (PFM) strength. The aim of the study was to do a systemic review of these methods for a better understanding of these techniques and to find the best appropriate method. A systemic review of the literature was done using three databases that included: PubMed, Scopus and Web of Science using the keywords "pelvic floor anatomy" and "functional anatomy of pelvic floor muscles" from 1985 to 2022. All the studies involved were analyzed for the methodologies used by the researcher, advantages, disadvantages, and the conclusion of the study. A total of 1,876 studies were found, out of which only 64 met the criteria of inclusion. In these studies, seven methods were used for the determination of PFM strength. These methods included: clinical palpation, perineometer, electromyography, dynamometer, ultrasonography, magnetic resonance imaging, and vaginal cones. The PFM cannot be calculated accurately using any one measuring technique. There is therefore no "gold standard" approach to PFM assessment. However, combining these methods will result in the best outcomes. According to the literature review, the most often employed procedures were digital palpation, perineometry, and Ultrasonography (USG).